AN ANALYSIS OF SPEECH ACTS IN ENGLISH DIALOGUE IN THE ANIME COWBOY BEBOP BY SHINICHIRO WATANABE - Gilang Kurnia Fazri; Usman Diennur; Handi Pabriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the types and functions of illocutionary speech acts found in the English-dubbed dialogue of the anime Cowboy Bebop (1998), directed by Shinichiro Watanabe. Framed within pragmatics and grounded in the speech act theories of Austin (1962) and Searle (1969, 1979), the research addresses two questions: what types of speech acts appear in the English dialogue of the anime, and what communicative functions each type performs. A qualitative content-analysis design was employed. Data were collected by watching the first eleven episodes of the series, transcribing the English dialogue of the four main characters (Spike Spiegel, Jet Black, Faye Valentine, and Edward), and coding each utterance according to Searle's five categories of illocutionary acts: assertive, directive, commissive, expressive, and declarative. The analysis identified 155 illocutionary utterances distributed as follows: directive (46), assertive (39), expressive (28), commissive (25), and declarative (17). A further functional analysis of 281 coded instances showed that assertive utterances were mainly used for asserting a belief, stating a fact, and concluding; directive utterances for requesting, commanding, and ordering; commissive utterances for offering, promising, and vowing; expressive utterances for apologizing, thanking, and congratulating; and declarative utterances for resigning and establishing a state. The findings confirm that directive and assertive acts dominate the characters' interaction, reflecting the high-stakes, action-oriented world of bounty hunting portrayed in the series, while expressive and commissive acts humanize the characters' relationships. The study contributes to pragmatic research on English-dubbed anime and offers pedagogical implications for using anime dialogue as authentic material in English language teaching.